2DI Report: Enhancing the resilience of climate-vulnerable households in Latin America - Álvarez, Sophie; Loboguerrero Rodriguez, Ana María; Martínez Barón, Deissy; Castellanos, Andrea; Valencia, Lina; Haan, Stef de; Loon, Jelle J. van; López Saavedra, Víctor (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
To start developing a demand-led research agenda – set the corresponding research and innovation priorities making sure that investments are targeted towards regional demands of a wide range of stakeholders and practitioners, including government programs, NGOs, farmer cooperatives, and the private sector – for addressing climate resilience in Central America and Central and Tropical Andes Hotspot.